ANALYSIS OF TAX AMNESTY IMPLEMENTATION IN TAX REVENUE IN ASIAN REGION COUNTRIES - Jati Hadipryanto; Siti Sarah; Tutty Nuryanti; Yeni Yeni; Rizqi Ramadhony; Armansyah Adhikara (Kesatuan Press, 2023)
Tax revenue has an unlimited useful life because taxes are collected from citizens as obligatory, and they can be forced to collect them. Taxes can support the development of a country. Tax amnesty is one of the fiscal policies to get tax revenue quickly. Several countries have implemented tax amnesty policies, but there have been successes and failures in their implementation. Information technology factors, as well as easy access to information and confidentiality guarantees, support the success of a tax amnesty. After implementing the (long-term) tax amnesty, tax revenues sometimes increase. It reflects that taxpayer compliance in reporting assets and depositing tax obligations is only sometimes obedient after implementing the tax amnesty program.